Little Wet-Paint Girl - Younsi, Ouanessa (Mingling Voices, 2022)
Born to a French-Canadian mother and Algerian father, Ouanessa Younsi is a bold and unique voice in modern Francophone poetry. In this intensely personal recitation on identity and ethnicity, Younsi takes the reader on a surreal odyssey through a liminal world of belonging and unbelonging, absence and presence, mind and body. Her visionary work, first published in French and translated here by Rebecca Thompson, is unsettling, riveting and guaranteed to leave readers contemplating the existential mysteries of "self."